2013
DOI: 10.3928/1081597x-20121217-01
|View full text |Cite
|
Sign up to set email alerts
|

Topography-guided Transepithelial PRK After Intracorneal Ring Segments Implantation and Corneal Collagen CXL in a Three-Step Procedure for Keratoconus

Abstract: Combined topography-guided transepithelial PRK with intracorneal ring segments implantation and CXL in a three-step procedure seems to be an effective, promising treatment sequence offering patients a functional visual acuity and ceasing progression of the ectatic disorder. A longer follow-up and larger case series are necessary to thoroughly evaluate safety, stability, and efficacy of this innovative procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 17 publications
0
45
0
5
Order By: Relevance
“…132 Hammer et al found a decreased stiffening effect with increasing UV-A intensity, also measured as comparative changes in Young's modulus at 10% strain. They found significant differences between 3 mW/cm2 vs. 9 mW/cm2, 3 mW/cm2 vs. 18 mW/cm2, and both 3 mW/cm2 and 9 mW/cm2 compared to the control M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 23 group, but no difference between 18 mW/cm2 and the control group. 53 In contrast to the standard protocol, in some studies the demarcation line is less dense, less uniform, and demonstrably present in fewer cases after equivalent accelerated treatments [ Figure 5].…”
Section: Varying the Treatment Time: Accelerated Cross-linkingmentioning
confidence: 99%
See 1 more Smart Citation
“…132 Hammer et al found a decreased stiffening effect with increasing UV-A intensity, also measured as comparative changes in Young's modulus at 10% strain. They found significant differences between 3 mW/cm2 vs. 9 mW/cm2, 3 mW/cm2 vs. 18 mW/cm2, and both 3 mW/cm2 and 9 mW/cm2 compared to the control M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 23 group, but no difference between 18 mW/cm2 and the control group. 53 In contrast to the standard protocol, in some studies the demarcation line is less dense, less uniform, and demonstrably present in fewer cases after equivalent accelerated treatments [ Figure 5].…”
Section: Varying the Treatment Time: Accelerated Cross-linkingmentioning
confidence: 99%
“…23 Long term follow-up will be important in these patients to determine the stability of visual outcomes.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The Ocular Wavefront Analyser and the Corneal Wavefront Analyser are reliable and have been recommended for use in refractive surgery, even though the Hartmann-Shack device was favored. 28 Although studies [12][13][14][15][16][18][19][20][21]23,34,35 have shown similar significant improvements in most of the tested visual functions, they have been conducted on a different population sample and/or have not agreed on all findings, partly because of the variation in the surgical protocol, and data collection/analysis method or follow-up duration. Additionally, many of these studies have been performed on a few eyes 15,16,20,21,23 and have used a format which is different from that recommended 25,26 in presenting their graphic data, thus making it difficult to directly compare results between studies.…”
Section: Discussionmentioning
confidence: 99%
“…7,9 However, a combination of various techniques such as conductive keratoplasty, 10 photorefractive keratectomy (PRK), [11][12][13][14] intrastromal corneal ring (ISCR) implantation plus PRK, 15,16 non-topography-guided PRK after ISCR implantation, 17 and simultaneous wavefront-guided PRK 18 with CXL maximizes the results by providing an overall additive effect on visual acuity, keratometry, and stability of the condition. 11,15,16,[19][20][21][22][23] Same-day simultaneous topography-guided PRK and CXL was shown to be superior to sequential CXL with later PRK in the visual rehabilitation of progressing keratoconus. 24 Despite the reported safety and improvements in visual functions associated with a same-day combined surgical approach, few studies have followed up the patients beyond 6 months postoperatively and the procedure is uncommon among practitioners in the Middle East despite the increasing number of keratoconus referrals.…”
mentioning
confidence: 99%
“…51 In a prospective case series of 16 eyes with progressive keratoconus, all patients underwent topography-guided transepithelial PRK after intracorneal ring segment implantation, followed by CXL treatment. This study showed significant improvement in visual acuity, refraction, and keratometry within 6 months after completion of the 3-step procedure.…”
Section: Combined Corneal Collagen Cross-linking and Refractive Surgerymentioning
confidence: 99%